Evolution of organic matter quantity and quality in a warm, hypersaline, alkaline lake: The example of the Miocene Nördlinger Ries impact crater, Germany - Zhao, Zibin; Grohmann, Sebastian; Zieger, Laura; Dai, Wanyu; Littke, Ralf (Frontiers in Earth Science, 2022)
The Nördlinger Ries (NR) impact crater in southern Germany contains Miocene lacustrine fine-grained post-impact sediments, which were deposited under saline, alkaline, and hydrologically closed aquatic conditions. To obtain information on the organic matter quantity, quality and environmental evolution, samples from one central (NR 1973) and one more marginal (Enkingen SUBO-18) well were analyzed by pyrolytic, organic geochemical and micro-petrographic techniques. Deposits of the marginal drilling can be linked to the thicker stratigraphic units of the well from the lake center based on total organic carbon (TOC), hydrogen index (HI) and lithology. Central deposits contain mainly hydrogen-rich type I kerogen with a mean HI of 447 mg HC/g TOC, whereas the marginal sequence contains type II-III kerogen with an average HI of 206 mg HC/g TOC. In the center, high total sulfur (TS) over TOC ratios of 1.5 on average, and δ13C values of biomarkers in combination with low α-/total MTTC (α-/total methyl-trimethyltridecyl chromans ∼ <0.6) and Pr/Ph ratios <0.2 suggest the prevalence of hypersaline water. Salinity only decreased during deposition of the uppermost Miocene units, when the then shallow alkaline lake turned, at least temporarily, into acidic-neutral conditions during the time of peat deposition. A similar trend, but at overall lower salinities is recorded for the marginal site. Water stratification in the center is stronger than in the marginal domain based on salinity variation. Anoxic bottom water prevailed in the whole lake, as recorded by exceptionally low Pr/Ph ratios (∼<0.2), the occurrence of des-A-lupane and small pyrite framboids (<5 µm) except for the youngest layers of the Miocene lake. Autochthonous, halophilic red algae/plankton prevailed as reflected by abundant C27 steranes, while terrestrial material and aerobic bacteria significantly contributed to the OM only in the latest stages of lake as evident from abundant vitrinite/inertinite particles, high values of diterpenes/C27 sterane (up to 255) as well as low values of C27-29 regular steranes/C29-32 hopanes (<0.5). The same trend, but less well resolved, can be seen at the margin of the paleo-lake.